1995
DOI: 10.1016/s0969-2126(01)00205-2
|View full text |Cite
|
Sign up to set email alerts
|

The low ionic strength crystal structure of horse cytochrome c at 2.1 å resolution and comparison with its high ionic strength counterpart

Abstract: Neither ionic strength nor crystal-packing interactions have much influence on the conformation of horse cytochrome c. Nevertheless, some differences in the side-chain conformations at high and low ionic strengths may be important for understanding how the protein functions. Close examination of the gamma-turn (residues 27-29) conserved in cytochromes c leads us to propose the 'negative classical' gamma-turn to describe this unusual feature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
1
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 38 publications
7
62
1
4
Order By: Relevance
“…This behavior may affect the affinity between two proteins. Indeed, it has been observed that, by increasing the ionic strength of the solution, the affinity between cyt c and cyt b 5 decreases [61]. This may be related to changes in the overall electrostatic interaction energy, but the present study shows that there are indeed specific changes in the conformation of key residues involved in the interaction.…”
Section: Discussioncontrasting
confidence: 49%
“…This behavior may affect the affinity between two proteins. Indeed, it has been observed that, by increasing the ionic strength of the solution, the affinity between cyt c and cyt b 5 decreases [61]. This may be related to changes in the overall electrostatic interaction energy, but the present study shows that there are indeed specific changes in the conformation of key residues involved in the interaction.…”
Section: Discussioncontrasting
confidence: 49%
“…These exhibit the same dominant features as the earlier measurements at low pH in strong saline solution (18). We have performed GNM calculations by using two different crystal structures (34,37) with PDB codes 1hrc and 1crc (at low ionic strength), obtained at 1.9 and 2.1 Å resolution, respectively. The heme group was not included in the calculations.…”
Section: Results and Comparison With Hx Experimentsmentioning
confidence: 56%
“…Lys-27, which takes part in forming an unusual ␥-turn (22), all other residues are within the permitted region. The skeleton of T-Cc is similar to that of horse heart Cc (hh-Cc; Protein Data Bank ID 1HRC) with the greatest rms deviations (rmsd) at the residue regions 1-5, 21-23, 37-46, 55-58, 85-87, and 96-104.…”
Section: Resultsmentioning
confidence: 99%